Introduction to Digital Policy Studies - Bhaso Ndzendze (Digital Policy Studies)
All over the world, governments, intergovernmental organisations, citizens and businesses are simultaneously driving, coping with and grasping the reality of digitalisation. They have promulgated new legislation, published plans, and put out strategies to pursue their brand of accelerated or perpetual development with the aid of electronic equipment and software for communications and cyber-physical execution. These entities have also used technologies to regulate, circumvent and/or contest one another. In the wake of these realities, new concepts have been introduced in the literature and the practitioner’s manuals and the citizen’s everyday lexicon. From agriculture to banking, culture, diplomacy, electric grids, finance, governance, human rights, international trade, and journalism, technologies are pushing the frontier of what was previously possible. With new capabilities and the proliferation of technologies such as artificial intelligence, big data, blockchain, and quantum computing, the process is receiving a significant jolt. Importantly, however, the benefits (convenient and efficient access to goods, services, information and ideas) are not even or universal. Neither are the side effects (climate change, exclusion, and e-waste, among others). Geographical, economic, and other realities reinforce old divides and give rise to new ones. But there are also instances of the gap being closed.